Eco-enzyme Produce Training for Dasawisma XI members in Banyuraden Village - Faizah, Restu; Widodo, Wahyu; Pratama, Wahyu Arif; Istiningsih, Istiningsih (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Waste management is still a major topic in environmental issues because the growth in waste production is much higher than its utilization. Moreover, population growth in Indonesia continues and causes the amount of waste increasing continues. One of the very large amounts of waste is organic waste which is the remains of vegetables or fruits. Organic waste can be processed into several useful products, such as eco-enzyme, bath soap, fertilizer, and others. This service activity aims to improve participants’ abilities in processing organic waste. The activities consists of two stages, namely counselling about awareness of shorting waste and training in processing organic waste into eco enzymes. The training participants were members of the Dasawisma XI, Banyuraden Village, totaling 24 people. After the activity, the participants are motivated to can start processing their own organic waste and produce eco enzyme. This activity is also expected to be an initial activity for the initiation of a waste bank.